2011
DOI: 10.1002/esp.2137
|View full text |Cite
|
Sign up to set email alerts
|

A parameterization of the wavelength of tidal dunes

Abstract: The idealized model of Besio et al. (On the formation of sand waves and sand banks. Journal of Fluid Mechanics 2006; 557: 1-17) is used to predict the wavelength of tidal dunes (sand waves) generated by tidal currents in estuaries and shallow seas. The predictions are then analysed and a formula is proposed to estimate the wavelength of tidal dunes as a function of the parameters of the problem. The wavelength of the dunes is found to increase when the water depth is increased and/or the strength of the tidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The correlations between sand wave frequency and water depth showed both positive and negative correlations, and this contrast may be explained from the varying wave impact. A previous modeling study without surface waves by Blondeaux and Vittori () found a negative relation between water depth and sand wave frequency. This is consistent with our results in the southern area.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The correlations between sand wave frequency and water depth showed both positive and negative correlations, and this contrast may be explained from the varying wave impact. A previous modeling study without surface waves by Blondeaux and Vittori () found a negative relation between water depth and sand wave frequency. This is consistent with our results in the southern area.…”
Section: Discussionmentioning
confidence: 82%
“…Hulscher and Van den Brink (2001) and Van der Veen et al (2006) compared modeled sand wave occurrence to observations in the North Sea and found good agreement with important contributions for grain size, depth, and flow velocity. A modeling study by Blondeaux and Vittori (2011) showed that sand wavelengths increase for larger water depths and smaller tidal flow velocities. Grain size and ellipticity of the tide did not show clear relations to sand wavelength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To explain the differences in sand wave behaviour at the three sites, we made use of available model studies that describe the initial formation of sand waves using linear stability analysis (Besio et al, 2003;Van Santen et al, 2011;Blondeaux and Vittori, 2011;Campmans et al, 2021). This theory assumes that initially there are only small bedforms, whose amplitudes grow or decay exponentially in time, with rates that are independent of their initial amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, applied geometrical relations to compute the sand wave height from sand wavelengths that were obtained with a processbased model. Blondeaux and Vittori (2011) used a process-based model to compute the sand wavelength for different values of the water depth and tidal current amplitude. From these outcomes, they presented empirical relations between water depth, tidal current strength and the sand wavelength.…”
Section: Empirical Modelsmentioning
confidence: 99%